2004
DOI: 10.1111/j.1399-6576.2004.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Women report more pain on injection of a precurarization dose of rocuronium: A randomized, prospective, placebo‐controlled trial

Abstract: Women experienced more pain on injection of rocuronium than men, moreover this is an additional evidence for gender-related differences in pain perception. When rocuronium is used as a precurarization agent, an analgesic pretreatment (e.g. opioids) should be considered, especially for female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
3
22
1
Order By: Relevance
“…This finding is consistent with the results of Chiarella et al [21] and Turan et al [22]. Mencke et al [7] and Tuncali et al [8] showed that rocuronium diluted with saline decreased injection pain significantly. However, in our study, there were no differences between the saline-mixed group (group 2) and the rocuronium only group (group 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the results of Chiarella et al [21] and Turan et al [22]. Mencke et al [7] and Tuncali et al [8] showed that rocuronium diluted with saline decreased injection pain significantly. However, in our study, there were no differences between the saline-mixed group (group 2) and the rocuronium only group (group 1).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that prior administration of lidocaine or fentanyl reduces rocuronium injection pain [4][5][6]. In recent studies with awake patients who received no pretreatment with local anesthetics or opioid, normal saline mixtures decreased rocuronium injection pain because of a dilution effect [7,8]. Dexmedetomidine [9], ketamine [10], and thiopental sodium [11] pretreatments also reduce pain on injection.…”
Section: Introductionmentioning
confidence: 95%
“…Though not associated with adverse clinical consequences for the patient's outcome, the incidence and the degree of pain and withdrawal reactions in response to the injection of rocuronium is significantly higher in women than in men 11 . The same implies for precurarization dose of rocuronium 12 .…”
Section: Discussionmentioning
confidence: 66%
“…Mencke et al [18] found a 33% incidence of pain using a precurarization dose of rocuronium of 0.03 mg/kg in 5 mL saline. We used a greater concentration, 0.05 mg/kg in 5 mL saline, and the frequency of pain was 63%.…”
Section: Discussionmentioning
confidence: 99%